P30-58 Extraction and Evaluation of Latent Representations from Peripheral Blood Smear Images - T. Iwasaka; T. Mizuno; K. Morita; I. Azuma; E. Nakashima; H. Kusuhara (Toxicology Letters, 2025)

P03-12 Network-Based Modeling of Immune Cell Interactions to Elucidate the Mechanisms of Toxicity - I. Azuma; T. Mizuno; H. Kusuhara (Toxicology Letters, 2025)

P12-08 Establishment of a novel and simple drinking water liver injury model for hepatotoxicity research - T. Iwasaka; T. Mizuno; K. Morita; I. Azuma; T. Nakagawa; E. Nakashima; H. Kusuhara (Toxicology Letters, 2024)

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Height-related variations of leaf traits reflect strategies for maintaining photosynthetic and hydraulic homeostasis in mature and old Pinus densiflora trees - Wakana Azuma; H. Roaki Ishii; Takashi Masaki (Oecologia, 2019)

Erratum to: Function and structure of leaves contributing to increasing water storage with height in the tallest Cryptomeria japonica trees of Japan - Wakana Azuma; H. Roaki Ishii; Katsushi Kuroda; Keiko Kuroda (Trees, 2016)

Function and structure of leaves contributing to increasing water storage with height in the tallest Cryptomeria japonica trees of Japan - Wakana Azuma; H. Roaki Ishii; Katsushi Kuroda; Keiko Kuroda (Trees, 2016)

Interspecific hybridization of fig (Ficus carica L.) and Ficus erecta Thunb., a source of Ceratocystis canker resistance - H. Yakushiji; T. Morita; S. Jikumaru; H. Ikegami; A. Azuma; Y. Koshita (Euphytica, 2012)

Breeding system, colony and population structure in the weaver ant Oecophylla smaragdina - E.A. SCHLÜNS; B.J. WEGENER; H. SCHLÜNS; N. AZUMA; S. K. A. ROBSON; R. H. CROZIER (Molecular Ecology, 2009)
Weaver ants ( Oecophylla smaragdina ) are dominant ants in open forests from India, Australia, China and Southeast Asia, whose leaf nests are held together with larval silk. The species, together with its sole congener O. longinoda , has been important in research on biological control, communication, territoriality and colony integration. Over most of the range, only one queen has been found per colony, but the occurrence of several queens per nest has been reported for the Australian Northern Territory. The number of males mating with each queen is little known. Here we report on the colony structure of O. smaragdina using published and new microsatellite markers. Worker genotype arrays reflect the occurrence of habitual polygyny (more than one queen per colony) in 18 colonies from Darwin, Northern Australia, with up to five queens inferred per colony. Monogyny (one queen per colony) with occasional polygyny was inferred for 14 colonies from Queensland, Australia, and 20 colonies from Java, Indonesia. Direct genotyping of the sperm carried by 77 Queensland queens and worker genotypic arrays of established colonies yielded similar results, indicating that less than half of the queens mate only once and some mate up to five times. Worker genotype arrays indicated that queens from Java and the Northern Territory also often mate with more than one male, but less often than those from Queensland. A strong isolation‐by‐distance effect was found for Queensland samples. The variation uncovered means that O. smaragdina is a more versatile study system than previously supposed.

Salmon gonadotropes secrete free form alpha (α)-subunit: quantitative analysis by the sandwich cell immunoblot assay - N. Naito; Y. Koide; T. Yada; T. Azuma; H. Kawauchi (Fish Physiology and Biochemistry, 2003)

Floral scent chemistry of mangrove plants - H. Azuma; M. Toyota; Y. Asakawa; T. Takaso; H. Tobe (Journal of Plant Research, 2002)

Internal Distribution of Acid Materials within Snow Crystals - H. Fushimi; T. Kawamura; H. Iida; M. Ochiai; T. Nakajima; Y. Azuma (Water, Air, & Soil Pollution, 2001)

Transfer of symbiotic luminous bacteria from parental Leiognathus nuchalis to their offspring - M. Wada; N. Azuma; N. Mizuno; H. Kurokura (Marine Biology, 1999)

Cardiac profile of EGIS-9377, a novel cardiotonic agent as a Ca2+ sensitizer with bradycardiac activity - Y. Hattori; T. Ishitani; F. Tomita; S. Gando; H. Yokoshiki; M. Azuma; O. Kemmotsu; M. Kanno (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Interaction of citrus juices with pranidipine, a new 1,4-dihydropyridine calcium antagonist, in healthy subjects - K. Hashimoto; T. Shirafuji; H. Sekino; O. Matsuoka; H. Sekino; O. Onnagawa; T. Okamoto; S. Kudo; J. Azuma (European Journal of Clinical Pharmacology, 1998)

The effect of Y-25510 injection on the serum levels of some cytokines in healthy adult volunteers - J. Azuma; M. Ogura; I. Yamamoto; M. Hisadome; T. Fukuda; Y. Ikeda; H. Mori; T. Oka; S. Asano (European Journal of Clinical Pharmacology, 1998)

The treatment with differentiation- and apoptosis-inducing agent, vesnarinone, of a patient with oral squamous cell carcinoma - M. Sato; K. Harada; Y. Yura; M. Azuma; H. Kawamata; H. Iga; H. Tsujimoto; H. Yoshida; M. Adachi (Apoptosis, 1997)

Therapy for oral squamous cell carcinoma by tegafur and streptococcal agent OK-432 in combination with radiotherapy: Association of the therapeutic effect with differentiation and apoptosis in the cancer cells - M. Sato; K. Harada; H. Yoshida; Y. Yura; M. Azuma; H. Iga; T. Bando; H. Kawamata; Y. Takegawa (Apoptosis, 1997)